EVALUATING THE DISTANCE LEARNING IN THE PANDEMIC ERA: A CASE STUDY AT FINANCIAL EDUCATION AND TRAINING AGENCY MAKASSAR - Azwar Iskandar; Achmat Subeka (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The objectives of this research were to: (i) evaluate the trainees’ satisfaction with trainers and training performance; (ii) evaluate learning gain or the improvement of trainees’ skills, knowledge, and attitudes after training; and (iii) identify the significant obstacles that reduced the effectiveness of the training. This study was conducted using the Kirkpatrick Evaluation Model through questionnaires, interviews, and descriptive statistical methods. This research revealed that: (i) the overall aspect of the implementation evaluation assessed by participants was in the Good category, although it could not meet the level of participants’ expectations. This could be seen from the ratio of the average total perception/reality to the average importance, which was below 100%. On the other hand, it was found that the trainers were able to meet the participants’ expectations, with the category of Very Good; (ii) the results of the evaluation analysis at Level 2 (learning gain) indicated that most participants graduated with a Good predicate and experienced an increase in scores. Thus, it could be asserted that participants gained additional knowledge after attending the training; and (iii) there were some obstacles faced by participants in attending the training, although in general the evaluation results showed positive outcomes. In terms of administration, participants generally complained about inadequate internet quality in some areas. Meanwhile, based on the trainers’ aspect, participants suggested that trainers add more case studies and raise more up-to-date issues in handling problems related to the training materials.